La culture de l’annulation entre quête de justice et débordement - Belghith, Nawel (Symbolon, 2022)
The Cancel Culture Between Quest for Justice and Overflow Cancel culture has developed in the various arts in multiple facets in order to publicly denounce individuals, groups or institutions responsible for acts, behaviours or remarks considered inadmissible or despicable by human society. Even if the concept of "the cancel culture " appeared at the end of the 2010s. Thus, more than an awareness strategy, the objective of the cancel culture in the arts is part of a real confrontation and continual struggle to minimize the impact of groups and behaviours that threaten modern societies. Since September 11, 2001 and the attacks on the twin towers of the World Trade Center and the Pentagon, several directors have chosen to fight against religious fanaticism and terrorism by directing films that denounce Islamic fundamentalism and fanaticism in all its forms. The appearance of Daesh in Syria and Iraq has led to the proliferation of cinematographic works that denounce the brutality, religious fanaticism and terrorism of this terrorist group. However, we note that a large part of the cinematographic works and successful series have attached the label of terrorist to Muslims and to the inhabitants of the Arab-Muslim world. In other words, by fighting against certain behaviours and stereotypes, some of the filmmakers have contributed to creating new stereotypes and nourishing them through artistic creations that stigmatize a particular religious category. We will first seek to present the different social representations of the phenomenon of cancel culture in popular culture and on social networks. In this first part, we will demonstrate the role of the cancel culture in delivering justice to victims in new, less legal and more instantaneous forms. Secondly, we will illustrate through different cinematographic examples how the concept of the cancel culture has led to the appearance of films and series that denounce intolerance, religious fundamentalism and terrorism. Finally, we will focus on the limits of this concept which has overflowed in several artistic representations to turn into the stigmatization and lynching of a particular social and religious category.